Transforming Nursery Education : SAGE Publications. - Moss, Peter (SAGE Publications Ltd, 1996)
`This is an important publication, which I urge colleagues to read and to consider carefully all the implications′- Early Years `... this provocative analysis with its clear examples is worth reading for its fresh look at where we could be headed come the 21st century′- Nursery Equipment Early childhood services in the UK have been badly neglected. The consequences are serious: chronic underfunding and increasing fragmentation; most staff poorly paid and trained; access often a matter of potluck and money; low aspirations and even lower expectations. Increasingly, young children are seen as important for what they may become rather than for what they are, and the.